FEMINISM OF WOMEN'S ROLE IN ENGLISH TEXTBOOK â€œENGLISH ON SKY 2 FOR GRADE VIIIâ€ - MULIANI MAHARA; MUHAMMAD NATSIR (State University of Medan, 2023)
This study aims to finding out the roles of women represented in pictures in the English textbook. Since the demand for gender equality or women's emancipation orÂ feminism has developed women can do some things and jobs that are usually done by men.This study uses a qualitative descriptive method and uses Peterson's 2004 theory to show the role of women in pictures. the results found are 29 images that represent the role of women. The results found were from 4 types of Peterson's theory which said the concept of the role of women in the new era, namely 1). women's freedom , based on this type, the role of women represented in the book English on sky 2 totals 4 pictures, with a percentage of 14% 2). A woman's obligation to herself, amount found 5 pictures, with a percentage of 17%.Â 3). A woman's obligation to her family, amount found 18 pictures with a percentage of 62% and 4). Education and seclusion, the amount found are 2 pictures with a percentage of 7%. It is hoped this research will be useful for readers who want to learn about the role of women